Students’ Learning Outcome In Physics: Predictive Power Of Split-Half Attention And Dual-Processing In Working Memory - Barnabas Ellah; Emmanuel Achor; Caroline Cem; Beguin Sophie (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
The study determined the predictive power of split-half attention and dual-processing in working memory on students’ learning outcome in Physics. The population for the study comprised 5138 science students in public senior secondary schools. The sample was 650 SSII students currently offering Physics as a school subject in 22 secondary schools in the study area. Three sets of instruments used for data collection were Attention Lapses Clicker (ALC), Force Concept Inventory (FCI) and Cognitive Reflection Test (CRT). The instruments were face validated by three experts. Estimate of internal consistency was obtained through Kuder-Richardson (K-R21) for FCI with coefficient of internal consistency as 0.73. Data normalization was done using ZT-score and T-score. The data collected were analyzed using regression analysis to answer research questions and test null hypotheses at 0.05 level of significance. It was spotlighted that split-half attention as well as dual-processing in working memory had significant predictive power on students’ learning outcome in Physics. Similarly, the combination of split-half attention and dual-processing in working memory had significant predictive power on students’ learning outcome in Physics. Based on these findings, it was recommended among others that Physics teachers should guide students to gain control of attention and action to facilitate and mandate encoding of stimulus into working memory for enhanced learning outcome in Physics. The information selected for students to be held in working memory should be relevant to current objectives of instructional delivery to reduce split-half attention effect and enhance learning outcome in Physics